Laboratory diagnostic outcome applying detection criteria recommended by the Scientific and Standardization Committee of the ISTH on Lupus Anticoagulant - Chantarangkul, Veena; Biguzzi, Eugenia; Asti, Daniela; Palmucci, Claudia; Tripodi, Armando (Thrombosis and Haemostasis, 2013)
This study shows the diagnostic outcome of an APTT-based and two dRVVT-based commercial confirmatory integrated tests with the application of the recommendations by the Scientific and Standardization Committee (SSC) on Lupus anticoagulant (LA)/antiphospholipid syndrome (APS) of the International Society on Thrombosis and Haemostasis (ISTH) issued in 2009 concerning the cut-off values for the screening, mixing and confirmatory tests for the detection of LA and the mandatory need to perform mixing tests of patient plasma with pooled normal plasma. The study population included 565 patients collected from a large central coagulation laboratory, for which the attending physicians requested LA detection. One-hundred-six healthy subjects (HS) and 131 selected patients on oral anticoagulant therapy (OAT) were included as negative controls. The results suggest that the performance of mixing tests is indicated for those methods with relatively poor specificity, but is less needed for those methods with high specificity. Furthermore, the SSC recommendation to use normal mid-value (i.e. the 50th percentile of distribution of results from healthy subjects) as the cut-off to interpret results of confirmatory tests, showed a modest increase in LA detection rate (sensitivity) but at the expense of specificity, particularly in methods with low specificity.
Keywords: Lupus anticoagulant; laboratory diagnosis criteria; cut-off values; mixing test